Logarithmically Complete Monotonicity of Certain Ratios Involving the \(k\)-Gamma Function - Nantomah, Kwara; Yin, Li (Communications in Mathematics and Applications, 2019)
In this paper, we prove logarithmically complete monotonicity properties of certain ratios of the \(k\)-gamma function. As a consequence, we deduce some inequalities involving the \(k\)-gamma function and the \(k\)-trigamma function.